2012
DOI: 10.1021/nn302694q
|View full text |Cite
|
Sign up to set email alerts
|

Tenside-free Preparation of Nanogels with High Functional β-Cyclodextrin Content

Abstract: We present the preparation of ultrafine (R(h), 50 -150 nm) nanogels through tenside-free condensation of reactive prepolymers with β-cyclodextrin (β-CD) in water. These nanogels possess a maximum content of 60 wt % functional β-CD that can form inclusion complexes as demonstrated by dye sorption with phenolphthalein. Aside of this extremely high uptake capacity to hydrophobic molecules, the nanogels also show good adhesion to surfaces in homogeneous distribution with size of R(h) of 25 nm under dry conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 32 publications
0
29
0
2
Order By: Relevance
“…Indeed, 12 kDa NCO-sP(EOstat-PO) may this way be used to form uniform nanoparticles that can for example be functionalized for high sequestration capacity of low molecular weight hydrophobic molecules. [24] Above a concentration of 5 w/w% when dissolving the macromer in water, homogeneous macroscopic hydrogels are formed with equilibrium water contents of at least 90%. SEM studies revealed that the hydrogels possess microporosity depending on the molecular weight of the precursor and the initial concentration in water (see Figure 1a-c for 12 kDa).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, 12 kDa NCO-sP(EOstat-PO) may this way be used to form uniform nanoparticles that can for example be functionalized for high sequestration capacity of low molecular weight hydrophobic molecules. [24] Above a concentration of 5 w/w% when dissolving the macromer in water, homogeneous macroscopic hydrogels are formed with equilibrium water contents of at least 90%. SEM studies revealed that the hydrogels possess microporosity depending on the molecular weight of the precursor and the initial concentration in water (see Figure 1a-c for 12 kDa).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, more tailored macromolecular approaches were subsequently pursued. [24] A macromolecular approach based on linear triblock copolymers of poly(tertbutyl glycidyl ether)-block-poly(ethylene oxide)-block-poly(tert-butyl glycidyl ether) (P(t-BuGEX-b-EOY-b-t-BuGEX); P1) and poly(glycidol)-block-poly(ethylene oxide)-block-poly(glycidol) (P(GX-b-EOYb-GX); P2), relied on additional crosslinking due to hydrophobic interaction (P1) or covalent bond formation through reaction with the NCO groups (P2). In both cases, the middle PEO-block was intended to serve as molecular spring for additional energy dissipation during mechanical load.…”
Section: Resultsmentioning
confidence: 99%
“…β-cyclodextrin (β-CD), a cyclic polysaccharide composed of seven glucose molecules could form a stable inclusion. Because of the special molecular structures-hydrophobic internal cavity and hydrophilic external surface, β-CD could combine with various guest molecules by the host-guest interaction (Kettel et al, 2012;Schofield and Badyal, 2011). The advantage of β-CD functionalization is that it offers high water solubility to GS (Mondal and Jana, 2012) and can be used as a carrier to capture a large amount of adamantine-1-carboxylic acid functionalized primary anti-AFP (ADA-Ab 1 ) by the host-guest interaction, which significantly improved the sensitivity of the electrochemical immunosensor.…”
Section: Introductionmentioning
confidence: 99%
“…57 In recent years, construction of one- and multidimensional nanoarchitectures using CDs as building blocks has attracted much attention, particularly due to their alluring potential in molecular machines 810 and functional materials. 1113 CD-based nanostructures integrate together a number of functional groups that have been already captured by CD cavities. These functional groups along with CD cavities provide multiple binding sites for substrates, allowing one to mimic the cooperative multimode complexation existing in biological systems widely.…”
Section: Introductionmentioning
confidence: 99%